Studi Pendahuluan terhadap Kemampuan Literasi Sains pada Pembelajaran Fisika Kelas XI SMAN 4 Padang - Yani, Siti Rahma Fitri; Akmam, Akmam (TSAQOFAH, 2025)
This preliminary study aims to analyze the level of scientific literacy among students in physics learning in Grade XI at SMAN 4 Padang. Scientific literacy is one of the essential 21st-century competencies, reflecting students’ ability to explain scientific phenomena, evaluate and design scientific knowledge, and interpret data and scientific evidence. A descriptive quantitative approach was employed, using a scientific literacy test instrument developed based on indicators from the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek). The research subjects consisted of 31 Grade XI students. The analysis results show that the average achievement in students’ scientific literacy was only 38.96%, with the following breakdown: explaining scientific phenomena (36.88%), evaluating and designing scientific knowledge (38.75%), and interpreting data and scientific evidence (41.25%). These findings indicate that students' scientific literacy skills remain low and do not meet the expected standards. Therefore, the study highlights the urgent need for the development of innovative physics learning models that enhance active engagement, conceptual understanding, and scientific thinking skills.